Identification of entomopathogenic fungi Metarhizium anisopliae and Purpureocillium lilacinum from oil palm plantation soils in Universiti Putra Malaysia - Sani, Ibrahim; Jamian, Syari; Ismail, Siti Izera; Saad, Norsazilawati; Abdullah, Sumaiyah; Mohd Hata, Erneeza; Kamarudin, Muhammad Amali; Jalinas, Johari (Malaysian Society for Microbiology, 2022)
Aims: Insect pests are one of the major constraints of oil palm production in Malaysia. However, synthetic chemical insecticides are the most common method for its control, despite their negative effects on non-target organisms and the development of resistance. Therefore, the present study is aimed to identify novel indigenous isolates of entomopathogenic fungi (EPF) in oil palm soil as part of integrated pest management (IPM) of oil palm insect pests. Methodology and results: The potential of EPF were isolated from the soil collected from the oil palm plantation in UPM using a mealworm beetle larva (Tenebrio molitor) as an insect bait. Seven Metarhizium anisopliae and two Purpureocillium lilacinum isolates were identified by morphological characterization (macroscopic and microscopic observation) and molecular identification using internal transcribed spacer (ITS) region (ITS region amplification). Conclusion, significance and impact of study: To our knowledge, this is the first time P. lilacinum has been found in the soil of an oil palm plantation or any other host in Malaysia. Furthermore, both of the isolates M. anisopliae and P. lilacinum may be potentially considered as biological control candidates for major insect pests in oil palm.